Comparative Study of the Antibacterial Activity of Algerian Honeys and Manuka Honey Toward Pathogenic Bacteria from Burn Wound Infections - Bouacha, M.; Besnaci, S.; Boudiar, I.; Буаша, М.; Бесначі, С.; Будіар, І. (PH "Akademperiodyka" of the NAS of Ukraine, 2023)
Objective. Honey is an extremely promising agent in the treatment of infected wounds of burned patients. This study aims to evaluate the antibacterial activity of 14 Algerian honey samples in comparison to Manuka honey towards pathogenic bacteria isolated from burn wound infections. Methods. The antibacterial effect of 14 Algerian honey samples and the Manuka honey was assessed against six multidrug-resistant bacteria: Escherichia coli, Pseudomonas aeruginosa, Klebsiella pneumoniae, Staphylococcus aureus, Staphylococcus saprophyticus, and Enterococcus faecalis. Well agar diffusion, microdilution broth assay, and time-kill assay were used to evaluate the effects of honey samples on the growth of pathogenic bacteria. Results. The results obtained show that all tested honey samples have good antibacterial effects and there is no significant difference between Algerian honey samples and Manuka honey, except honey samples H12 and H13. The Gram-positive bacteria were more susceptible to honey samples than Gram-negative bacteria. The inhibitory diameters were between 14 to 38 mm for Gram-positive bacteria and from 8 to 28 mm for Gram-negative bacteria. The minimal inhibitory concentration of Algerian honey was between 5 and 80% (v/v) and minimal bactericidal concentration was between 10 and 80 % (v/v). However, the minimal inhibitory concentration of Manuka honey was between 5 and 40% (v/v) and minimal bactericidal concentration was between 10 and 80% (v/v). The MBC/MIC ratio was from 1 to 2, which proves that both Algeria honeys and Manuka honey have a bactericidal effect rather than a bacteriostatic effect. A time-kill assay showed that the inhibition effect of honey samples started after the first 3 hours of incubation. Honey samples 3 and 7 inhibited the growth of S. aureus and S. saprophyticus in 15 hours; however, they inhibited the growth of the other pathogenic bacteria in 18 hours. Conclusions. This study proposes honey as an extremely promising treatment against multidrug-resistant bacteria from burn infections.